KEEFEKTIFAN PROGRAM GERAKAN SERENTAK MEMBANGUN KAMPUNG (GSMK) DALAM MEMBERDAYAKAN MASYARAKAT PEDESAAN DI KECAMATAN RAWA PITU KABUPATEN TULANG BAWANG - Saputra, Hendra; Effendi, Irwan; Nikmatullah, Dewangga (Lampung University, 2016)
This study aims to analyze: 1) level efectiveness of GSMK program in empowering rural communities at Rawa Pitu Subdistrict Tulang Bawang Regency, and 2) factors that have relation with effectiveness of GSMK program in empowering rural communities at Rawa Pitu Subdistrict Tulang Bawang Regency.Â These researches were conducted at Rawa Pitu Subdistrict Tulang Bawang Regency. Samples of this study amount to of 53 respondents randomly. Data analysis method used descriptive analysis, qualitatif, tabulation and Rank Spearman correlation.Â The results showed: 1) level of effectiveness GSMK program in empowering rural communities at Rawa Pitu Subdistrict Tulang Bawang Regency it has been well, because the specific purpose of GSMK program had been achieved and GSMK program also couldÂ create satisfaction and pride for the result they had been done, and 2) factors that have relation with effectiveness of GSMK program at Rawa Pitu Subdistrict Tulang Bawang Regency were societyâs level of knowledge about GSMK program, societyâs attitude about GSMK program and role of Pokmas in GSMK program. Key words: effectiveness, empowering, GSMK program, society